Analysis of differential gene expression in the brain tissue transcriptome of Jiangkou radish piglets infected with porcine pseudorabies virus - Wei Sun; Shan-Shan Liu; Yu Fan; Sheng-Qing Deng; Hua-Qi Zhang; Fengzhao Zhu; Shi-He Long; Tao-Hua Ren; Ling Bai (SAGE Open Medicine)
Background: The research focused on the effects of pseudorabies virus on gene expression in piglet brain tissue. Objectives: The goal was to understand the changes in gene expression in piglet brains due to pseudorabies virus infection. Design: The study used a comparative approach with infected and control piglet groups. Methods: Twelve 2-month-old piglets were divided into pseudorabies virus-infected and PBS-treated control groups, with brain tissue analyzed after 7 days. Results: Infected piglets showed increased oligodendrocyte counts and pseudorabies virus-positive signals. Transcriptomic analysis revealed 269 differentially expressed genes, with 149 up-regulated and 120 down-regulated. Gene ontology and Kyoto Encyclopedia of Genes and Genomes analyses indicated these genes are involved in signal transduction, transmembrane transport, apoptosis, and neuroactive ligand–receptor interaction. Quantitative fluorescent PCR validated these findings, particularly for genes related to neuroactive pathways, ferroptosis, and IL-17 signaling. Conclusion: The study provides valuable insights into the molecular alterations caused by pseudorabies virus in piglet brain tissue, enhancing our understanding of pseudorabies virus’s pathogenic mechanisms.